Menentukan Kelayakan Pelayanan Service Advisor Pada PT. Sutan Indo Aneka Mobil Pematangsiantar dengan Metode Weighted Sum Model - Siahaan, Mian Manimpan; Damanik, Irfan Sudahri; Saragih, Ilham Syahputra (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Service becomes one of the important things in the form of business activities engaged in services. Worthiness in providing the best service must be through a good judgment. There are company indicators in assessing the feasibility of service advisor at PT. Sutan Indo Aneka Mobil Pematangsiantar. This requires a method to be able to assist the company in making decisions (MCDM). Weighted Sum Model (WSM) method is the best solution to help companies in determining the feasibility of service with many criteria